BIVI APPLICATION IMPLEMENTATION FOR WARDAH BEAUTY ADVISORS IN KUALA TANJUNG, NORTH SUMATRA - Mhd Abdillah; Cut Izzara; Nadiya Nadiya; Fitri Lisna Yani; Anwar Anwar; Intan Cahyani Rachman; Zulfikar Zulfikar (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
This study aims to analyze the implementation of the BIVI (Beauty in Virtual Identity) application on the performance of Wardah Beauty Advisors at Toko Butet Joni Kuala Tanjung Batubara. The research method used is descriptive qualitative with a case study approach. Data were obtained through observation, in-depth interviews, and documentation studies. The results show that the BIVI application contributes to improving operational efficiency through online attendance features based on geolocation and real-time sales recording, which facilitate performance monitoring, payroll calculation, and product stock management. However, the study also found obstacles such as technical issues related to internet stability and limited employee understanding of the application workflow. Overall, the implementation of the BIVI application has a positive impact on enhancing employee performance and can serve as a reference for the development of technology-based management systems in the future.